Mind the gaps: functional networks disrupted by white matter hyperintensities are associated with greater falls risk - Crockett, Rachel A.; Hsu, Chun Liang; Dao, Elizabeth; Tam, Roger; Alkeridy, Walid; Eng, Janice J.; Handy, Todd C.; Liu-Ambrose, Teresa (Neurobiology of aging, 2022)
•Lesion network mapping identifies functional networks associated with falls risk•WMH-related disruption to the DAN is associated with greater falls risk•WMH-related disruption to the SMN and VAN are associated with foam sway•Physical activity moderates the association between the DAN and falls risk White matter hyperintensities (WMH) are associated with greater falls risk and slow gait speed. Whether these deficits are caused by the disruption of large-scale functional networks remains inconclusive. Further, physical activity moderates the association between WMHs and falls, but whether this extends to the disruption of functional networks remains unknown. One hundred and sixty-four adults (>55 years old) were included in this study. Using lesion network mapping, we identified significant correlations between the percentage of WMH-related disruption of the dorsal attention network and Physiological Profile Assessment (PPA) score (r = 0.24, p < 0.01); and between disruption of both the sensorimotor (r = 0.23, p < 0.01) and ventral attention networks (r = 0.21, p = 0.01) with foam sway. There were no significant associations with floor sway or gait speed. Physical activity moderated the association between the dorsal attention network and PPA score (p = 0.045). Thus, future research should investigate whether physical activity should be recommended in the clinical management of older adults with cerebral small vessel disease.